A discrete-choice experiment to assess treatment modality preferences of patients with anxiety disorder. (1st February 2019) - Lokkerbol, Joran; van Voorthuijsen, Julia M.; Geomini, Amber; Tiemens, Bea; van Straten, Annemieke; Smit, Filip; Risseeuw, Anneriek; van Balkom, Anton; Hiligsmann, Mickaël
Abstract: Aims: The aim of this study was to elicit the preference of patients with an anxiety disorder regarding treatment modalities. Understanding patients' preferences could help optimize treatment uptake and adherence to therapeutic interventions. Materials and methods: A discrete-choice experiment was used to elicit patients' preferences with regard to four treatment characteristics: waiting time until first treatment, intensity of treatment, face-to-face vs digital treatment, and group size. In 12 choice sets, participants were asked to choose between two treatment alternatives. A random parameters logit model was used to analyse the data. Results : A total of 126 participants, aged 18 years and older, currently or in the previous year in treatment for an anxiety disorder, completed the survey. Respondents preferred short (over long) waiting times, face-to-face (over digital) treatment, individual (over group) treatment and a treatment intensity of one session per week rather than two sessions per week or one session every two weeks. Waiting time and treatment intensity were substantially less important to patients than level of digitalization and group size. Heterogeneity in preference was significant for each attribute, and sub-group analyses revealed this was partly related to education level and age. Limitations: The convenience sample over-represented the female and younger population, limiting generalizability. Limited information on background characteristics limited the possibilities to explore preference heterogeneity. Conclusions: This study demonstrated how different treatment components for anxiety disorders affect patients' preferences for those treatments. There is significant variation in treatment preferences, even after accounting for age and education. Incorporating patients' preferences into treatment decisions could potentially lead to improved adherence of treatments for anxiety disorders.